A comparative performance analysis on daylighting for two different types of solar concentrators: Dish vs. Fresnel lens. (15th October 2017) - Kim, Yeongmin; Jeong, Hae Jun; Kim, Wonsik; Chun, Wongee; Han, Hyun Joo; Lim, Sang Hoon
Abstract: This study introduces the experimental work done to analyze the performance of active daylighting systems, which consist of small individually operated solar concentrators. Each system is capable of precise solar tracking thanks to the double axis solar tracker designed and constructed for lightness and easy operation. A solar tracking algorithm was implemented with AVR based on both closed and open loop control algorithms. Two different types of solar concentrators (developed for the system) were tested to assess their photometric characteristics in collecting and delivering solar rays to a deep plan office space for better lighting. To measure illuminance at different times of the day, a number of photo sensors were installed on the task planes at a height of 85 cm above the floor. The luminance values on different walls (including task planes) were also measured at a regular interval of 30 min to assess their variation with time and solar altitude. These photometric data enabled a systematic performance evaluation of the systems employed in the present study. The experimental results demonstrated the applicability of the daylighting systems employed in this work in bringing natural daylight to the interior, especially, to those spaces too deep for conventional daylighting apertures. Highlights: Two different types of solar concentrators are compared for daylighting performance. A series of measurements were performed side by side for an actual office space. Some practical suggestions are made when using a daylighting system in view of energy efficiency. Results are introduced leading to an innovative fiber optic system to harvest daylight in buildings.